SHARI‘AH-COMPLIANT FINANCE AND FINANCIAL INCLUSION: A CRITIQUE OF PALLIATIVE MEASURES ON THE REMOVAL OF FUEL SUBSIDY IN NIGERIA - Ayinla-Edun, Mohd Jamiu (Jurnal Syariah, 2024)
Fuel is an essential commodity whose availability, affordability, and otherwise affect the market prices of virtually all other essential goods and services. It is empirically observable that the high price of fuel will undoubtedly contribute to the increasing prices of other fundamental needs such as food and transportation. This scenario will bring about undue hardship and a decline in the standard of living of any country. The foregoing informed the reason why the Nigerian government, over time, subsidized the price of fuel, especially the Premium Motor Spirit. However, due to high-level corruption and maladministration of the subsidy regime in Nigeria, the government deemed it expedient to remove the subsidy and allow market forces to determine the selling price. The removal expectedly affected the financial ability of Nigerians, as all goods and services, especially transportation, witnessed a drastic hike in prices. Thus, the incumbent government had to roll out its palliative plans and measures to ameliorate the suffering caused by the subsidy removal and ensure the financial uplifting of Nigerians. The palliative measures for micro, small, and medium enterprises (MSMEs) and start-ups, however, raised concerns of marginalization and exclusion of Nigerians who, due to faith or other convictions, are opposed to any financial arrangement that is not Sharī‘ah compliant. This research, therefore, combined doctrinal and empirical methodologies to critique the palliative measures for MSMEs and start-ups set out by the Nigerian government, with the view to determining their Sharī‘ah compliance and whether or not they have fostered financial inclusion, especially from an Islamic perspective. The research found that the fuel subsidy removal palliative occasioned financial exclusion rather than the desired inclusion due to non-compliance with Sharī‘ah parameters. The work recommends, among others, a revisiting of the scheme to ensure it is Sharī‘ah compliant.